The Influence of Social Media Marketing Instagram, Word of Mouth and Brand Awareness of Purchase Decisions on Arthenis Tour and Travel - Novita Alfian; Sengguruh Nilowardono (IJEBD International Journal Of Entrepreneurship And Business Development eISSN 2597-4785 pISSN 2597-4750)
The purpose of this study is to analyze the extent of Social Media Marketing Instagram, Word of Mouth, and Brand Awareness of purchasing decisions at Arthenis Tour and Travel. This study uses primary data obtained from customer answers. The instrument uses a questionnaire with a Likert scale. The population in this study are 105 Arthenis Tour and Travel consumers and taking a sample of 83 people. The hypothesis is used with multiple linear regression tests. Based on the results of the study, obtained the value of Fcount (198,348) > Ftable (2,72) related to simultaneous and partial on Social Media Marketing Instargram, Word of Mouth and Brand Awareness of the expected variables as a result of purchase. It is expected for travel agents can support their Instagram, using Word of Mouth and Brand Awareness so they can increase their sales.